THE ROLE OF QUTLAR, PRINCE OF MANGAQUTI, IN THE RIVALRIES AND INTERNAL STRUGGLES OF THE ILKHANATE (680–698 AH / 1281–1298 AD) - Farhan, Sarmad; Omer, Othman (Humanities Journal of University of Zakho, 2025)
The current study sheds light on the role of one of the most important Prince and leaders of the history of Mongolian Ilkhanate country in Iran: he is Prince Qutlugh, the son of Manghuhdaye of the Mangaquti tribe who were Mongolians. In fact, according to many studies, the role of Prince Qutlugh Shahi was prominent at the time of Elikhan Abaqa the son of Hulagu (663-680Mishakhty/1265-1282AD). It is worth mentioning that his presence as a fierce and tough leader in the Elikhan military forces has not come out of nowhere. This is because his ancestors had their own influential position from Jangizkhan times and till the time of Hulagu. However, during the time of Elikhan Gazani, Qutlugh Shahi became the most important figure in a very crucial manner. This is because it is evident that at the time of Elikhan Gazani the Gazanis faced many military attacks and betrayal attempts took place and in all of these attempts he could conquer the enemy which made him the number one figure in protecting the Elikhan Gazani authorities. He was also one of those people who were very powerful and brave and with his support Gazani managed to reach the throne of authority following the overthrown of Baydo the son of Torgay in (694m/1295AD). In addition to protecting the authority of Elikhan Gazani due to a number of attacks, interior movements, and other betrayal plans against Elikhan Gazani, we can argue that Prince Qutlugh Shah was a great military leader in a very sensitive and critical phase in protecting the authorities of Gazani from all interior and exterior attempts.